Plasma inflammation‐related biomarkers are associated with intrinsic capacity in community‐dwelling older adults. Issue 2 (20th January 2023) - Lu, Wan‐Hsuan; Gonzalez‐Bautista, Emmanuel; Guyonnet, Sophie; Lucas, Alexandre; Parini, Angelo; Walston, Jeremy D.; Vellas, Bruno; de Souto Barreto, Philipe; ,
Abstract: Background: How inflammation relates to intrinsic capacity (IC), the composite of physical and mental capacities, remains undefined. Our study aimed to investigate the cross‐sectional and longitudinal associations between plasma inflammation‐related biomarkers and IC in older adults. Methods: This secondary analysis of the Multidomain Alzheimer Preventive Trial (MAPT) included 1238 community‐dwelling older individuals with IC assessments from 12 to 60 months. Plasma C‐reactive protein (CRP), interleukin‐6 (IL‐6), tumour necrosis factor receptor‐1 (TNFR‐1), monocyte chemoattractant protein‐1 (MCP‐1) and growth differentiation factor‐15 (GDF‐15) were measured at 12 months. IC was operationalized as a score ranging from 0 to 100, derived from four domains: cognition, Mini‐Mental State Examination ; locomotion, Short Physical Performance Battery ; psychological, Geriatric Depression Scale ; and vitality, handgrip strength . A five‐domain IC score (plus sensory) was investigated in a subsample ( n  = 535) with a 1‐year follow‐up as an exploratory outcome. Results: The mean age of the 1238 participants was 76.2 years (SD = 4.3); 63.7% were female. Their initial four‐domain IC scores averaged 78.9 points (SD = 9.3), with a yearly decline of 1.17 points (95% CI = −1.30 to −1.05; P  < 0.001). We observed significant associations of lower baseline IC with higher CRP, IL‐6, TNFR‐1 and GDF‐15, after controlling age, sex, MAPT group allocation and educational level [ CRP: adjusted β (95% CI) = −1.56 (−2.64 to −0.48); P  = 0.005; IL‐6: adjusted β = −3.16 (−4.82 to −1.50); P  < 0.001; TNFR‐1: adjusted β = −6.86 (−10.25 to −3.47); P  < 0.001; GDF‐15: adjusted β = −7.07 (−10.02 to −4.12); P  < 0.001]. Higher TNFR‐1, MCP‐1 and GDF‐15 were associated with faster decline in four‐domain IC over 4 years [ TNFR‐1: adjusted β (95% CI) = −1.28 (−2.29 to −0.27); P  = 0.013; MCP‐1: adjusted β = −1.33 (−2.24 to −0.42); P  = 0.004; GDF‐15: adjusted β = −1.42 (−2.26 to −0.58); P  = 0.001]. None of the biomarkers was significantly associated with the five‐domain IC decline. Conclusions: Inflammation was associated with lower IC in older adults. Among all plasma biomarkers, TNFR‐1 and GDF‐15 were consistently associated with IC at the cross‐sectional and longitudinal levels.